2015
DOI: 10.1016/j.diagmicrobio.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of antibody responses to multiple antigens from Mycobacterium tuberculosis in active and latent tuberculosis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
11
1
1
Order By: Relevance
“…Any prior comparable study on anti-MtM IgG antibodies is not available, whereas available studies on the anti-Acr IgG antibodies have reported equivocal findings. According to some, their levels are low in ATB and high in LTBI [24,28,30] and, according to some others, these levels are high in ATB and low in LTBI [21,25,29,41]. While demographic differences in study populations could have led to such diverse results, differences in antibody assay protocols (discussed below) may also have contributed to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any prior comparable study on anti-MtM IgG antibodies is not available, whereas available studies on the anti-Acr IgG antibodies have reported equivocal findings. According to some, their levels are low in ATB and high in LTBI [24,28,30] and, according to some others, these levels are high in ATB and low in LTBI [21,25,29,41]. While demographic differences in study populations could have led to such diverse results, differences in antibody assay protocols (discussed below) may also have contributed to it.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to active TB disease, persons with LTBI have shown a stronger T cell response to Acr [21][22][23] which was not influenced by BCG vaccination [23]. High levels of anti-Acr antibodies have been reported in TB patients and their contacts [21,24,25], HCWs exposed to Mtb [26] and cerebrospinal fluid of patients with tuberculous meningitis [27]. Conversely, some studies have found lower antibody levels in active than in inactive or latent TB [28].…”
Section: Introductionmentioning
confidence: 99%
“…The LTBI group comprised subjects with documented exposure to persons with confirmed TB and positive responses to a tuberculin skin test or INF‐γ release assay (QuantiFERON‐TB Gold In‐Tube test, Cellestis, Chadstone, Vic, Australia) in the absence of clinical or radiographic evidence of TB. The subjects’ medical histories, physical and laboratory examination results were obtained as described previously . HCs had no TB‐related symptoms and their tuberculin skin tests, INF‐γ release assays and radiography findings were negative.…”
Section: Methodsmentioning
confidence: 99%
“…This interest in humoral immunity in Mtb is evidenced by a mounting number of studies that have identified specific antibody targets, and structural or functional differences that are observed during different TB disease states (26)(27)(28)(29)(30). For example, while Mtb-specific IgG titers alone have been insufficient in distinguishing between latent and active TB, refinement of these correlates using additional isotypes, subclasses, and other Fc modifications are underway (see Figure 1) (31)(32)(33)(34)(35). Moreover, incorporating data including multiple instead of single Mtb antigens as well as Fab affinity and avidity to Mtb targets may improve sensitivity and specificity (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%